2017
DOI: 10.1080/20008198.2017.1390362
|View full text |Cite
|
Sign up to set email alerts
|

Transdiagnostic culturally adapted CBT with Farsi-speaking refugees: a pilot study

Abstract: Background: Approximately half of all asylum seekers suffer from trauma-related disorders requiring treatment, among them Posttraumatic Stress Disorder (PTSD), depression, anxiety, and somatic symptoms. There is a lack of easily accessible, low-threshold treatments taking the cultural background into account. Culturally Adapted CBT (CA CBT) is a well evaluated, transdiagnostic group intervention for refugees, using psychoeducation, meditation, and Yoga-like exercises. Objective: An uncontrolled pilot study wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
37
0
4

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 45 publications
(43 citation statements)
references
References 40 publications
(64 reference statements)
2
37
0
4
Order By: Relevance
“…Yet, these studies have been conducted on non-refugee populations. Other promising approaches could be writing exercises as already used by Kalantari and colleagues in bereaved Afghani refugees [51] or an adaption of culturally adapted CBT as seen in Hinton and colleagues [52].…”
Section: Discussionmentioning
confidence: 99%
“…Yet, these studies have been conducted on non-refugee populations. Other promising approaches could be writing exercises as already used by Kalantari and colleagues in bereaved Afghani refugees [51] or an adaption of culturally adapted CBT as seen in Hinton and colleagues [52].…”
Section: Discussionmentioning
confidence: 99%
“…The trauma-informed yoga was added to the programme to enhance emotional regulation skills and stress regulation by means of bodily control during the intensive treatment (Kananian, Ayoughi, Farugie, Hinton, & Stangier, 2017; Yehuda et al, 2017). The protocol was adapted from ‘Trauma-sensitive yoga’ (Emerson & Hopper, 2011) and the ‘Yoga for the mind’ programme (Mason, 2011).…”
Section: Methodsmentioning
confidence: 99%
“…A previous pilot study by our group in a sample of Afghan refugees also showed promising results, with a significant reduction of general psychopathological distress (Kananian et al, 2017). A major limitation of this pilot was its lack of a control group.…”
mentioning
confidence: 74%
“…A power analysis was calculated using G * Power (Faul et al, 2007) and based on an F test model. We based the calculation on the primary outcome of the initial pilot trial of culturally adapted CBT (Kananian et al, 2017) and prior trials by Hinton et al (2005Hinton et al ( , 2011, which yielded a Hedges' g effect size of 2.5 and Cohen's d effect sizes of 3.8 and 3.0, respectively. For the comparison of the treatment condition and the randomized waitlist control condition, we expected a Cohen's d effect size of 2.0 or an f value of 1.…”
Section: Discussionmentioning
confidence: 99%